2010
DOI: 10.2741/e210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidural and systemic maternal analgesia in term infants the NoPiL study

Abstract: The aim of the No Pain in Labour (NoPiL) study was to evaluate the stress and clinical outcome of infants vaginally born without maternal analgesia and after maternal epidural or systemic analgesia. We studied 120 healthy term infants, 41 in the no analgesia group, 38 in the epidural analgesia group, and 41 in the systemic analgesia group. Cortisol, beta-endorphin, oxidative stress markers (ie: total hydroperoxide (TH) and advanced oxidation protein products (AOPP)), interleukin-1beta (IL-1beta), and interleuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…26-29 These studies also show marked variability that appears to be influenced by obstetrical intervention and mode of delivery. 30-32 Consistent with these findings in our preterm population, covariates of medical intervention (e.g., artificial ROM, tocolysis, c-section delivery) all had odds ratios <1.0 with elevated 8-IP, suggesting a protective effect. Conversely, covariates related to ongoing labor (preterm labor, spontaneous ROM and prolonged ROM) were positively associated with elevated 8-IP (OR>1, data not shown).…”
Section: Discussionsupporting
confidence: 84%
“…26-29 These studies also show marked variability that appears to be influenced by obstetrical intervention and mode of delivery. 30-32 Consistent with these findings in our preterm population, covariates of medical intervention (e.g., artificial ROM, tocolysis, c-section delivery) all had odds ratios <1.0 with elevated 8-IP, suggesting a protective effect. Conversely, covariates related to ongoing labor (preterm labor, spontaneous ROM and prolonged ROM) were positively associated with elevated 8-IP (OR>1, data not shown).…”
Section: Discussionsupporting
confidence: 84%
“…Previous researchers have reported that EA affects not only the process of labor but also the newborn, detecting an increase in the percentage of newborns requiring resuscitation and hospitalization in the neonatal intensive care unit that was associated with EA administration (Herrera-Gómez et al, 2015). Investigators have also reported that EA affects the biochemical profile of newborns, increasing their cytokine levels (Dani et al, 2010). Also, Bell, White-Traut, Wang, and Schwertz (2012) explored relationships between exposure to EA and maternal and umbilical cortisol.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous report, anesthesia and analgesia do not affect the health state of the newborn, as indicated by Apgar score; cord blood pH; the occurrence of hypoglycemia, hyperbilirubinemia, and respiratory depression; the lack of changes in the levels of cortisol, beta-endorphin, and two oxidative stress markers (total hydroperoxide and advanced oxidation protein products) in the cord arterial blood and extremely high levels of 2 cytokines (IL-1 beta and IL-8) in the epidural analgesia group. ( 18 ) Although numerous previous studies have examined the association between pregnancy and oxidative stress, evidence that maternal anesthesia affects the condition of the fetus or neonate is lacking. ( 19 ) While a certain amount of reactive oxygen species (ROS) is necessary for normal embryonic and fetal development, an excess of ROS or oxidative stress is associated with maternal obesity, smoking and hypertension.…”
Section: Discussionmentioning
confidence: 99%